2018
DOI: 10.18857/jkpt.2018.30.6.229
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Pilates Exercise Using the Three Dimensional Schroth Breathing Technique on the Physical Factors of Scoliosis Patients

Abstract: This study aims to verify the effects of Pilates exercise using the three-dimensional (3D) Schroth breathing technique on scoliosis patients in comparison with the existing Pilates exercise technique, which uses lateral breathing. Methods: The subjects were 16 scoliosis patients who went to S fitness center in Daegu, Korea. They were randomly and equally divided into a Schroth Pilates exercise group (SPEG), who performed Pilates exercise using 3D Schroth breathing, and a Pilates exercise group (PEG) who perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…The effect of Pilates on ATR (°) was assessed in 2 studies [ 24 , 32 ] (n = 146). On the basis of their findings, they reported that Pilates may have some benefit in improving trunk rotation (SMD = 1.37, 95% CI = 1.01–1.73; I 2 = 0%, P < .001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of Pilates on ATR (°) was assessed in 2 studies [ 24 , 32 ] (n = 146). On the basis of their findings, they reported that Pilates may have some benefit in improving trunk rotation (SMD = 1.37, 95% CI = 1.01–1.73; I 2 = 0%, P < .001) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Two trials evaluated the effect of Pilates on trunk ROM (°) [ 24 , 27 ] (n = 47). A higher ROM was provided by Pilates exercise training (SMD = 1.23, 95% CI = 0.45–2.00; I 2 = 28%, P = .002), and based on a randomized-effects model, there may be some benefit of Pilates exercise training on trunk ROM compared to the waiting list or breathing exercise (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Seo and Hong [9] observed a significant reduction in Cobb' s angle using X-ray imaging techniques to verify the effectiveness after 10 weeks of Pilates exercise in patients with scoliosis, and the effect of body alignment was confirmed by obtaining a significant decrease in Cobb's angle [8]. Pilates exercise has been reported to be effective not only in posture correction but also in relieving back pain [17].…”
Section: Discussionmentioning
confidence: 97%